Evaluation of International Language Centre (ILC) Bombong Ntala Labuan Bajo Regency - Elin Elin; Rr. Hasti Robiasih (Universitas Sarjanawiyata Tamansiswa, 2020)
This should be in one paragraph between 250-300 words. It must focus on: aims of the study, methods, findings, conclusions, and implications. This research aims to evaluate English Language Course of International Language Centre (ILC) Bombong Ntala Labuan Bajo Program particularly speaking skills based on the context, input, process, and product. This is an evaluation research that applied Stufflebeam's CIPP model (2007). The data were collected through observation, interview and document analysis. The data were analyzed using Miles, H. and Saldana’s flow model of qualitative data research that included data collection, data reduction, data display, conclusion, and verification. The findings revealed that evaluation in terms of Context evaluation, background of program vision and mission was supported to the context. The goal of ILC Bombong Ntala Course failed to meet the background, vision and mission because it did not promote the platform that aims to promote the institution to reach out more scopes of customers. Instead, it provided foreign languages courses (English and Spanish) to promote citizens’ language literacies, not only limited to such foreign languages, but also to create more possibilities for people to learn, for example, English for entrepreneurship, and English for tourism. In terms of Input evaluation, two teachers were not graduated from English department and the curriculum and syllabus of ILC Bombong Ntala Course show did not employ any determined curricula. The next evaluation is Process. The result of evaluation showed the processes of teaching and learning at the ILC Bombong Ntala Course could not run well. The last Product was the product evaluation. This evaluation proved that the outcome of English course program was not good effective enough to improve the students’ speaking skills.